1978
DOI: 10.1093/cvr/12.7.401
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the elasticity and characteristic impedance of the ascending aorta in man

Abstract: In 30 patients, simultaneous measurements of ascending aortic pressure and diameter were performed, allowing one to evaluate: (1) the influence of age, the aortic diastolic pressure, and the radius on the aortic elasticity; (2) the correlations between characteristics impedance of the aorta (Zo), systemic arterial resistance, age and diastolic aortic pressure; and (3) the importance of Zo when comparing two indices of left ventricle performance; one during isovolumic phase ([dP/dt]/Pt)max and the other during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
13

Year Published

1983
1983
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 0 publications
3
26
0
13
Order By: Relevance
“…Therefore, the PWV is proportional to the square root of Ep. It has been shown that Ep increases with pulse pressure, and the rate of increase is higher in older subjects compared to young subjects (2). The Ep estimated with our method is actually the average Ep over the whole range of pulse pressures.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Therefore, the PWV is proportional to the square root of Ep. It has been shown that Ep increases with pulse pressure, and the rate of increase is higher in older subjects compared to young subjects (2). The Ep estimated with our method is actually the average Ep over the whole range of pulse pressures.…”
Section: Discussionmentioning
confidence: 72%
“…The spatial-temporal profiles in both the presystolic (Eq. [2]) and early systolic (Eq. [3]) phases were fitted with a linear function by a least-squares algorithm:…”
Section: Calculation Of Pwvmentioning
confidence: 99%
See 2 more Smart Citations
“…However, human studies are limited for methodological reasons, principally because of the invasive nature of evaluation techniques. 6 Recent progress in noninvasive echo Doppler ultrasound has enabled more adequate evaluation of the viscoelastic properties of large arteries by using transcutaneous measurements in situ. 7 -12 The geometry and the mechanical properties of specific arterial segments may be investigated in situ, but such studies have yielded poor results in patients with hypertension.…”
Section: A Noninvasive Study Of Carotid and Femoral Arteriesmentioning
confidence: 99%